To solve the equation \( 10.25 ( x - 4.4 ) - 69.7 = 2.4 \), we will first isolate the term containing \( x \).
-
Start with the equation: \[ 10.25 ( x - 4.4 ) - 69.7 = 2.4 \]
-
Add \( 69.7 \) to both sides: \[ 10.25 ( x - 4.4 ) = 2.4 + 69.7 \] \[ 10.25 ( x - 4.4 ) = 72.1 \]
-
Now divide both sides by \( 10.25 \): \[ x - 4.4 = \frac{72.1}{10.25} \] \[ x - 4.4 = 7.0239 \]
-
Next, add \( 4.4 \) to both sides: \[ x = 7.0239 + 4.4 \] \[ x = 11.4239 \]
Now let's check the options:
- 2.4
- 11.2
- 63.85
- 6.8
None of the options match \( 11.4239 \). Thus it seems there is an error in the provided options or the original equation.
Would you like me to check for a mistake or assist further?